Trends in colorectal cancer incidence and related lifestyle risk factors in 15–49-year-olds in Canada, 1969–2010. (June 2016) - Patel, Parth; De, Prithwish
Highlights: We analyzed trends in incidence of colorectal cancer in young adults in Canada. Incidence rate for colorectal cancer has been increasing since the mid-1990's in young adults. We analyzed trends in modifiable risk factors for colorectal cancer in Canada. The prevalence of excess weight has also been increasing in young adults. Excess weight may have likely played a role in rising colorectal cancer incidence. Abstract: Background: While the overall incidence rate of colorectal cancer (CRC) in Canada has been decreasing, some countries show an increasing incidence in those under the age of 50. We examined the trends in CRC incidence and associated lifestyle risk factors in Canadians aged 15–49. Methods: Incidence data for colorectal, colon and rectum/rectosigmoid cancers were obtained for 1969–2010 from the Canadian Cancer Registry, and trends in age-standardized incidence rates (ASIRs) were examined by Joinpoint regression for three age groups (15–29, 30–39, 40–49 years) and by sex. Trends in the prevalence of some CRC risk factors were similarly examined from national health surveys for various periods ranging from 1970 to 2012. Results: In both sexes combined, ASIRs rose by 6.7%/year (1997–2010) for 15–29-year-olds, 2.4%/year (1996–2010) for 30–39-year-olds, and 0.8%/year (1997–2010) for 40–49-year-olds. Similar trends were observed by sex. The rise in ASIR was more rapid for cancers of the rectum/rectosigmoid compared to colon for all age groups. Risk factor trends varied: excess weight rose substantially, vegetables and fruit consumption increased slightly, physical inactivity rates declined but remained high, alcohol consumption changed little, and smoking rates declined. Data on red/processed meat consumption were unavailable. Conclusion: The ASIR of CRC in young Canadians has increased since about the mid-1990s. The rising prevalence of excess weight in younger generations has likely played a role in the CRC trend, but more research is needed.